HIV primary care providers—Screening, knowledge, attitudes and behaviors related to alcohol interventions. (1st April 2016) - Chander, Geetanjali; Monroe, Anne K.; Crane, Heidi M.; Hutton, Heidi E.; Saag, Michael S.; Cropsey, Karen; Eron, Joseph J.; Quinlivan, E. Byrd; Geng, Elvin; Mathews, William Christopher; Boswell, Stephen; Rodriquez, Benigno; et al.
Highlights: We surveyed HIV providers on their alcohol screening and treatment practices. The majority of HIV providers report routinely screening for alcohol use, though fewer reported using a formal screening tool. Fewer providers provide pharmacotherapy for alcohol use. Lack of knowledge is cited as a barrier to the use of pharmacotherapy in HIV clinics. Abstract: Background: Alcohol has particularly harmful health effects in HIV-infected patients; therefore, HIV clinics are an important setting for integration of brief alcohol intervention and alcohol pharmacotherapy to improve patient outcomes. Current practices of alcohol screening, counseling, and prescription of pharmacotherapy by HIV providers are unknown. Methods: We conducted a cross-sectional survey of HIV providers from 8 HIV clinical sites across the United States. Surveys queried knowledge and use of alcohol screening, brief advice, counseling and pharmacotherapy, confidence and willingness to prescribe pharmacotherapy and barriers to their use of alcohol pharmacotherapy. We used multivariable logistic regression to examine provider factors associated with confidence and willingness to prescribe pharmacotherapy. Results: Providers ( N = 158) were predominantly female (58%) and Caucasian (73%); almost half were infectious disease physicians and 31% had been in practice 10–20 years. Most providers (95%) reported always or usually screening for alcohol use, although only 10% reported using a formal screening tool. Over two-thirds never or rarely treated alcohol-dependent patients with pharmacotherapy themselves. Most (71%) referred alcohol-dependent patients for treatment. Knowledge regarding alcohol pharmacotherapy was low. The major barrier to prescribing pharmacotherapy was insufficient training on use of pharmacotherapy. Provider confidence ratings were positively correlated with their practice patterns. Conclusions: HIV providers reported high rates of screening for alcohol use, though few used a formal screening tool. Most providers referred alcohol dependent patients to outside resources for treatment. Few reported prescribing alcohol pharmacotherapy. Increased training on alcohol pharmacotherapy may increase confidence in prescribing and use of these medications in HIV care settings.